ERH: a plug‐and‐play protein important for gene silencing and cell cycle progression. (5th November 2022) - Graille, Marc
Abstract : In metazoans, most proteins have pleiotropic cellular functions and have the ability to interact with several factors to accomplish these different functions. This is the case of eukaryotic ERH proteins, a family of homodimeric proteins involved in DNA replication and cell cycle control as well as in gene silencing by contributing either to the biogenesis of small interference RNAs (miRNAs, piRNAs) or to the recruitment of RNA decay machineries. Very recently, several crystal structures describing complexes formed by eukaryotic ERH proteins and several small peptides from various partners have highlighted the existence of different binding sites on the surface of ERH proteins. In this issue of The FEBS Journal, Wang et al. present the crystal structure of the complex formed between the human ERH protein and a short peptide of the CIZ1 protein, one of its partners. Altogether, this information will be particularly important for future studies aimed at dissecting the different biological functions governed by this family of highly conserved proteins. Comment on: https://doi.org/10.1111/febs.16611 Abstract : Several recent crystal structures of eukaryotic ERH proteins – a family of homodimeric proteins involved in DNA replication, cell cycle control and gene silencing – complexed with small peptides from various partners, indicate binding sites on the surface of ERH proteins. In this issue, Wang et al. present the crystal structure of human ERH complexed with a short peptide of the CIZ1 protein, one of its partners. Such information is crucial for dissecting the biological functions of ERH proteins. Comment on: https://doi.org/10.1111/febs.16611